EXTERNAL DEBT AND ECONOMIC GROWTH IN GHANA: A CO-INTEGRATION AND VECTOR ERROR CORRECTION ANALYSIS - ASAFO, Shuffield Seyram; MATUKA, Adelajda (Theoretical and Practical Research in Economic Fields; Vol 10 No 1 (2019): TPREF, Volume X, Issue 1(19), Summer 2019, 2019)
This paper employed a co-integration analysis and an error correction methodology to examine the impact of external debt on economic growth in Ghana using annual time series for the period 1970-2017. We found that external debt inflows spur growth in Ghana both in the long-run and short-run. Secondly, our study also confirmed the crowding out effect and the non-linear effect of external debt in the long run and short-run. However, Debt overhang was only confirmed in the short-run. We advocate for a judicious allocation of the debt resources so that the cost of servicing the debt will not outweigh the benefit of the borrowed funds.